Effect of Inflation on Export Earnings in Uganda (1990-2022). - Eyanu, Daniel (Kabale University, 2024)
This quantitative study aimed to examine the effect of Inflation on Export Earnings in Uganda from 1990-2022 while controlling exchange rates, Inflation, and Trade Openness. The study employed a quantitative approach with Descriptive Correlational Design to analyze secondary time series data generated from the World Development Indicators to test the relationship between exchange rates, Tariff rates, and Inflation on export earnings. The study results from the correlation, Regression, and Cointegration analysis found the existence of a significant relationship between Inflation and Export Earnings over 1990-2022, there was no significant relationship between Real Exchange Rate and Export Earnings over 1990-2022 and there was no significant relationship between Tariff Rates and Export Earnings over 1990-2022. Regarding the main objective, the study concluded that Inflation had a significant negative effect on Export Earnings hence necessitating the control of the level of Inflation in the Country to ensure improvement in efficiency of the Export sector in Uganda. Finally, this study recommends that further research investigate the effect of Inflation on the Balance of Payments in the Case of Uganda over various periods. This study can be cited as, Eyanu (2024).